2018
DOI: 10.1002/pssr.201800171
|View full text |Cite
|
Sign up to set email alerts
|

Quasi‐White Light‐Emitting Devices Based on SiC Quantum Dots

Abstract: White electroluminescence based on quantum dots (QDs) is usually realized by incorporating different types of QDs or QDs plus rare earth ion phosphors into a single device. Herein, we report quasi-white electroluminescence in pure silicon carbide QDs-based light-emitting devices (LEDs). The carrier transport and recombination mechanisms are investigated through analyzing the current density versus bias curves and spatial distribution of energy levels. The carrier transport mechanism is dominated by quantum tun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 53 publications
(82 reference statements)
0
3
0
Order By: Relevance
“…The reduction in SiC size to the nanoscale level provides outstanding mechanical, physical, and chemical properties due to quantum confinement effects. For example, Chen et al [ 3 ] synthesized 1.9–4.5 nm SiC quantum dots (QDs) via an electrochemical etching method and used them as emitting layers in LEDs. They exhibited a significant enhancement in electroluminescence performances, dominated by carrier transports from quantum tunneling at a low voltage.…”
Section: Introductionmentioning
confidence: 99%
“…The reduction in SiC size to the nanoscale level provides outstanding mechanical, physical, and chemical properties due to quantum confinement effects. For example, Chen et al [ 3 ] synthesized 1.9–4.5 nm SiC quantum dots (QDs) via an electrochemical etching method and used them as emitting layers in LEDs. They exhibited a significant enhancement in electroluminescence performances, dominated by carrier transports from quantum tunneling at a low voltage.…”
Section: Introductionmentioning
confidence: 99%
“…The surface of SiC accommodates diverse surface reconstruction and termination with corresponding defects such as bridge and triple-bonded C/Si dimers, which generate fruitful surface states in the band gap. Hence, the SiC surface has attracted great interest. , As the dimension of the semiconductor SiC is reduced to the nanoscale, its surface structure becomes even more complex, the dangling bonds of the active carbon and silicon atoms of the freshly prepared SiC quantum dots (QDs) can readily be passivated by oxygen and hydrogen atoms to form quite fruitful bonding structures. The resultant surface states in the band gap can actively participate in the photon absorption and emission processes. The whole surface passivation layer becomes a two-dimensional quantum system, which in combination with quantum confinement and the intentionally created interior point defects determines the photodynamics , and charge transport properties of the SiC QDs. Therefore, understanding the surface structures and characteristics of the SiC QDs is critical for realizing their better applications in biological labeling, solid-state lighting, and quantum spintronics. Our previous study indicates that the CO bonds on the SiC QD surface generate surface-localized orbitals and contribute to the blue fluorescence; however, the role of the silicon–oxygen bonds in fluorescence of the SiC QDs remains unclear. In contrast, wide investigations have revealed that the SiO fluorescence (590 nm, 2.1 eV) is the dominant surface-state fluorescence of the Si QDs .…”
Section: Introductionmentioning
confidence: 99%
“…Although SiC is an indirect‐bandgap semiconductor with low quantum yield, SiC quantum dots (QDs) exhibit bright and wavelength‐tunable fluorescence as their sizes approach or are smaller than bulk Bohr exciton diameter due to quantum confinement effect . Therefore, the SiC QDs can be used as stable light sources for sensors, cell imaging, and light‐emitting diodes . On the other hand, the surface of the SiC QD offers fruitful emission colors owing to existence of various surface defect‐related luminescence centers .…”
Section: Introductionmentioning
confidence: 99%